2013
DOI: 10.1002/asl2.444
|View full text |Cite
|
Sign up to set email alerts
|

What is the relationship between China summer precipitation and the change of apparent heat source over the Tibetan Plateau?

Abstract: It is well documented that the East Asian summer monsoon has been experiencing a steady weakening trend in recent decades. Because the Asian summer monsoon (including both East Asian monsoon and South Asian monsoon) is the largest and most pronounced monsoonal system in the world, its change in strength may exert a profound impact on global weather and climate systems, especially on the rainfall pattern in South and East Asia. On the other hand, as a vast elevated landmass, the Tibetan Plateau forms a huge hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 25 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…These changes are no doubt a combination of natural variability and anthropogenic influences and are variable across the large territory of China. The collocation of the transition in China's large‐scale topography and southwesterly monsoonal flows leads to a climate‐fragile and environment‐fragile belt in China, which can experience drying or wetting trends depending on the increase or decrease in EASM variability [ Xu et al ., ]. The climate changes of China have been documented in many publications that are too numerous to list, but good summaries can be found in the IPCC reports [ IPCC , , , ], Ding et al .…”
Section: Aerosols and Climate Change In Asia: An Observational Perspementioning
confidence: 99%
“…These changes are no doubt a combination of natural variability and anthropogenic influences and are variable across the large territory of China. The collocation of the transition in China's large‐scale topography and southwesterly monsoonal flows leads to a climate‐fragile and environment‐fragile belt in China, which can experience drying or wetting trends depending on the increase or decrease in EASM variability [ Xu et al ., ]. The climate changes of China have been documented in many publications that are too numerous to list, but good summaries can be found in the IPCC reports [ IPCC , , , ], Ding et al .…”
Section: Aerosols and Climate Change In Asia: An Observational Perspementioning
confidence: 99%
“…The Tibetan Plateau, known as the Third Pole, is the highest plateau in the world with an average elevation above 4 km (Qiu, ). The latent and sensible heat over the Tibetan Plateau play a significant role on the weather and climate in the Asian monsoon region, even globally (Wu and Zhang, ; Liu and Chen, ; Wu et al , ; Xu et al , , ; Zhong et al , ; Zhu et al , ). As a strong heat source in the summer, it is thought that the Tibetan Plateau controls the Asian summer monsoon systems through thermal forcing (Liu et al , ; Wu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…And the diminished heat island effect on the TP serves to reduce the land-sea thermal contrast, resulting in a weakened monsoon and a "south floods north drought" pattern. Previous studies have shown that strong heating of the TP changes the structure of water vapor transport to East Asia, as well as the spatial and temporal variation of summer monsoon precipitation (Xu et al 2013).…”
Section: Connections To Rainstorm Activity In Eastern Chinamentioning
confidence: 99%